PENGARUH HARGA TIKET, FASILITAS OBJEK WISATA, DAN KEAMANAN TERHADAP MINAT BERWISATA DI OBJEK WISATA TELAGA NGEBEL - Nurdiana Nurdiana; Adi Santoso (Jurnal Riset Entrepreneurship, 2023)
The purpose of this study was to determine the effect of ticket prices, tourist attraction facilities, and security on tourist interest in the Ngebel Lake tourist attraction. This research is quantitative research. The population for this study was visitors to the Ngebel Lake tourist attraction, totaling 14.767 in the period of October 2022. The number of samples for this study was 99 which was determined using the slovin formula. The sampling method used is accidental sampling. The analytical method used is multiple linear regression analysis. The results of this study found that ticket prices, tourist attraction facilities, and security partially had a significant effect on tourist interest in the Ngebel Lake tourist attraction.